The Vicksburg assaults, May 19-22, 1863 - Woodworth, Steven E.; Grear, Charles D., 1976- (Civil War campaigns in the West, 2019)
"The first anthology to examine the two Union assaults on Confederate defensive lines around the city of Vicksburg, Mississippi, the volume is not limited to the exact dates of the campaign and extends to the months after the assaults. Ranging in scope from military to social history, the book both examines in detail the two assaults and furthers historical debates on topics such as the differing perspectives of the fighting at the Railroad Redoubt and the reactions of Midwesterners to the news of the assaults"--